2020
DOI: 10.1111/resp.13955
|View full text |Cite
|
Sign up to set email alerts
|

The impact of regular bisoprolol on the response to salbutamol in asthma: A double‐blind randomized placebo‐controlled crossover trial

Abstract: Background and objective: Non-selective beta-blockers impair the bronchodilator response to beta 2-agonists. Cardio-selective beta 1-blockers are less likely to cause this effect, yet they remain relatively contraindicated in asthma. We investigated whether the response to salbutamol is impaired during cardio-selective beta 1blocker treatment in people with asthma. Methods: A random-order, double-blind, placebo-controlled, non-inferiority, crossover study was conducted comparing up to 5 mg bisoprolol daily for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…A randomised placebo-controlled cross-over trial of 19 adults with mild or moderate asthma given bisoprolol daily for a minimum of 2 weeks found no difference in exacerbations between the groups. 37 Rescue beta-agonist therapy after a controlled bronchoconstriction was also non-inferior with bisoprolol treatment.…”
Section: Published Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…A randomised placebo-controlled cross-over trial of 19 adults with mild or moderate asthma given bisoprolol daily for a minimum of 2 weeks found no difference in exacerbations between the groups. 37 Rescue beta-agonist therapy after a controlled bronchoconstriction was also non-inferior with bisoprolol treatment.…”
Section: Published Reportsmentioning
confidence: 99%
“…24 However, the bronchodilator response to beta-agonist therapy is maintained during continuous treatment with cardio-selective beta 1blockers. [35][36][37]…”
Section: Interactions With Beta-agonist Therapymentioning
confidence: 99%
“…Less blockade of peripheral β 2 -adrenoceptors with a selective agent reduces the likelihood feelings of cold in the extremities [16][17][18] Controlled clinical trials of bisoprolol (vs. lisinopril [19]) and nebivolol (vs. metoprolol [20]) have demonstrated effective BP lowering, and no cause for concern regarding worsening of limb ischaemia Glycaemic control Many reports have described a worsening of glycaemic control during treatment with a β-blocker and use of a cardioselective agent helps to minimise these effects [17,18] The clinical significance of this phenomenon may have been overrated, however, worsened glycaemia may be unrelated to β-blockade [21],,and use of a β-blocker in a large diabetes prevention trial was not associated with increased risk of diabetes [22] Bisoprolol or nebivolol has not been associated with worsening of glycaemia [7,[23][24][25][26][27][28][29] Asthma and COPD Bronchospasm in patients with COPD or asthma may be exacerbated by blockade of β 2 -adrenoceptors in the smooth muscle of the airways [30] Non-selective β 1 -blockers, but not β 1 -selective agents, increase the risk of asthma exacerbations [31] A recent (2020) randomised, double-blind, crossover study confirmed that the bronchodilatory effects of bisoprolol were non-inferior during treatment with bisoprolol vs. placebo [32] Such findings have led to a reappraisal of the use of selective β 1 -blockers in patients with asthma or COPD [30,33]; β 1selective agents are no contraindicated in Europe only for "severe bronchial asthma" Erectile function β-blockers, have been associated with new or exacerbated erectile dysfunction [34], although neither bisoprolol nor nebivolol were associated with sexual dysfunction [35][36][37] Nebivolol improved erectile function vs. metoprolol [38,39], or atenolol (± chlorthalidone) [40] Another study demonstrated fewer patients reporting vs. not reporting sexual dysfunction on nebivolol vs. other β-blockers…”
Section: Peripheral Vasoconstriction and Pvdmentioning
confidence: 99%
“…A recent (2020) randomised, double-blind, crossover study confirmed that the bronchodilatory effects of bisoprolol were non-inferior during treatment with bisoprolol vs. placebo [ 32 ]…”
Section: Properties Of Bisoprolol and Nebivololmentioning
confidence: 99%
“…2 The recent publication in Respirology by Bennet et al and the Waikato research team has used a randomorder, double-blinded, placebo-controlled, non-inferiority, crossover study of 19 adults with mild to moderate asthma to demonstrate the safety of bisoprolol. 5 Bisoprolol is a β 1 -selective adrenoreceptor beta-blocker that is widely used for stable, chronic, moderate to severe heart failure. The study participants were adults with mild to moderate asthma as defined by Global Initiative for Asthma (GINA) 2018 Steps 1-2.…”
mentioning
confidence: 99%